Effective Vocabulary Teaching Strategies to Enhance EFL Learners' Reading Abilities: A Case Study - Nasri, Chahira (Universitas Siliwangi, 2022)
The past decades have witnessed an increasing focus on teaching vocabulary. Such interest includes all the aspects that are vital to enrich this important language element. The present research aims at highlighting the importance of incorporating effective vocabulary teaching strategies to enhance EFL learners' reading abilities by investigating the significant effect of vocabulary on improving reading abilities. It attempts to analyze the qualitative and quantitative data obtained from participants. Guided by the assumption that poor vocabulary creates problems for L2 learners and the claim of Macaro (2003) who believed that most second language teachers tend to neglect the significance of vocabulary teaching. This study adopted mixed-methods research to confirm our assumptions. The research instruments are a questionnaire submitted to one hundred and twenty first-year EFL learners in three Algerian universities, and a semi-structured interview with eight university teachers. The study used SPSS to analyse the data obtained from participants. The findings of this research reveal that teachers find obstacles when introducing new vocabulary to learners; however, they also reveal that are many strategies that can be followed to enlarge the lexis of L2. The study provides theoretical guidelines to enhance reading abilities since the latter is considered the main source of new vocabulary. Keywords: Vocabulary; Reading comprehension; Vocabulary teaching strategies.